Influence of social media use on life satisfaction among deaf and hard of hearing college students: a mediating role of self-esteem and perceived social support - Huang, Xinyi; He, Liang (Frontiers in Psychology, 2025)
IntroductionAs social media continues to gain popularity and living standards improve, people are becoming increasingly concerned with their quality of life, highlighting the importance and urgency of exploring the relationship between social media and well-being. At the meantime, the gap between majority and minority groups is widening in digital era. However, there is currently insufficient research on the use of social media by D/HH (Deaf or hard of hearing) individuals and its impacts. There is also a lack of international attention on China, which has the largest population of D/HH individuals.MethodsThe main objective of this research was to explore how social media use impacts D/HH college students’ well-beings, and this study recruited 320 Chinese hearing-impaired social media users and conducted a questionnaire survey using the SWLS (Satisfaction with Life Scale), MSPSS (Multidimensional Scale of Perceived Social Support), and RSES (Rosenberg Self-Esteem Scale) scales. The study delved into the reasons for social media use among this population, the relationship between social media use frequency and life satisfaction, and the potential mediating roles of self-esteem and perceived social support.ResultsThe findings revealed that the primary reasons for social media use among hearing-impaired individuals include communication, acquiring information and knowledge, and relaxation. Moreover, there is a positive correlation between social media use frequency and life satisfaction, perceived social support, and self-esteem, with both direct and indirect effects. These results align with earlier studies and our comprehension of how social media use boosts life satisfaction, potentially advancing research in this field.DiscussionThis paper explores in depth media accessibility, the mediating mechanisms of perceived social support and self-esteem, and their impacts on life satisfaction and other mental health issues of D/HH.